Cryptocurrency integration challenges in blockchain for financial institution - Islam, Md Rafiqul; Rahman, Muhammad Mahbubur; Rahman, Mohammed Ataur; Mohamad, Muslim Har Sani; Embong, Abd Halim (AlamBiblio Publishers, 2021)
Cryptocurrency is the latest adventure of currencies that works by using the new edge technology called the blockchain. It has gained the notable attention of the people for the last several years across the world. Cryptocurrency is also globally known as digital currency or virtual currency, and it is a form of payment that can be used online for goods and services. Blockchain has captured the application of many in the financial industry, including those vigorous in the transaction, clearing, and settlement, with its promise of greater efficiency and higher resiliency. The Cryptocurrency has been adopted by using blockchain technology that raised eye-catching attention in the financial sector, government, stakeholders, and individuals as well. It can be anticipated that Cryptocurrency will be the future currency that will replace fiat money worldwide. Though it has been attracted the users' attention, the money of them worried about its future useability, drawbacks, and challenges. Still, the research on cryptocurrencies is far behind and in the initial stage to integrate these currencies in financial institutes. This lack of trust situation in the financial sector aggravates further when it comes to cryptocurrency management challenges that are still not critically analyzed. The originality of this paper is the concept of currencies including cryptocurrencies, the concept of the blockchain ecosystem, and the cryptocurrency integration challenges of the existing blockchain in the financial institution. This paper will help the new researchers to work on cryptocurrencies and their integration challenges in the financial system.